TECHNIQUE TRANSLATION GATHERING POETRY "THERE ISN'T ANY NEW YORK BY M. AAN MANSYUR - Karunia Fauziah, Nadika; Sari Dewi, Ika (La Ogi : English Language Journal, 2024)
Translation of literary works has its own complexity and difficulties when compared to the translation of scientific texts. One example of a literary work is poetry. Poems that contain many meanings and figurative words must of course be translated well so that they can be understood by the target reader. This study aims to find out the translation techniques used in the collection of poems No New York Today by M. Aan Mansyur translated by John H Mcglynn into English. The The research method used in this study is qualitative research. The data analysis process in this research used five stages. The results of this study show that the technique used in the translation of M. Aan Mansyur's poems entitled "No New York Today" and "I Never Really Go Home" by John H Mcglynn from Indonesian to English is the usual modulation, establish equivalence, and adaptation